Diversity and distribution of taxa in the genus Eunotia Ehrenberg (Bacillariophyta) in Macedonia - Pavlov, Aleksandar; Levkov, Zlatko (Phytotaxa, 2013)
Within the past few decades Eunotia (Bacillariophyceae) has been confirmed as one of the most species rich diatom genera. The remarkable diversity of this genus has been well documented for the tropical region of South America, and its wide distribution comprehensively demonstrated for North America and Canada, Europe, East and Southeast Asia, as well as the Subantarctic region. Till present day only twenty eight taxa of Eunotia have been reported for Macedonia, mainly from the various aquatic habitats of different mountains. The main focus of the present study is the diversity, taxonomy and general distribution of taxa belonging to Eunotia in Macedonian mountain regions. The area investigated covers most of the mountains in the western, south-western, southern, central and eastern part. In total 53 taxa have been observed, among which six are described as new species (Eunotia atomus, E. fabaeformis, E. mariovensis, E. pseudominor, E. scardica and E. stojanovskii). The morphological features, as observed by light microscopy (LM), are comprehensively described for each taxon. The ultrastructure of the valve, as observed by scanning electron microscopy (SEM), is additionally described for most of the taxa. The general distributional pattern, locality, altitude and substrate preference, for every taxon is also included. The distinctive characters between similar taxa are discussed and taxonomical notes are as well provided.